TQM / ISO 9001 implementation in Northern and Central Luzon State Universities - De Leon, Patrick C. (The Journal of Public Affairs and Development, 2017)
This case study was conducted to investigate why and how the TQM/ISO 9001 programs were adopted in state universities in the Philippines such as Pangasinan State University, Nueva Ecija University of Science and Technology, and Central Luzon State University; what...